Ionic liquid aqueous solutions under nanoconfinement - Rodriguez, Javier (2012)
We extend our previous molecular dynamics analysis of confined aqueous electrolytes within cylindrical hydrophobic pores of nanometric dimensions [Videla et al. J. Chem. Phys.2011, 135, 104503] to the case of room temperature ionic liquid (RTIL) solutions, with concentrations close to c ∼ 1 M. Equilibrium and dynamical characteristics of two imidazolium-based RTILs, differing in the hydrophobicity of the corresponding anionic species, were considered. The solutions within the pore were modeled in contact with "bulk-like" reservoirs, which served as reference systems to gauge the magnitude of the modifications observed in the global densities and in the transport coefficients. The density fields associated to the ionic species present a marked enhancement near the pore walls; this leads to increments of the global RTIL concentration within the pores, which are intermediate between 2 and 3 times the ones observed in the bulk reservoirs. These modifications are more marked in solutions containing more hydrophobic anionic species. In both cases, selective adsorption of imidazolium groups at the pore walls prevails; these wall-solvation states are characterized by a parallel orientation of the imidazolium ring, with respect to the pore surface. Mass and charge transport were also investigated. The segregation of the ionic species towards the pore wall promotes a sharp drop in the individual ionic diffusion coefficients. Nonuniform trends in the modifications of the ionic conductivity were found. Our results show that charge transport is the result of a complex interplay between competing effects involving modifications in the local concentrations, retardations in the ionic mobility, and dynamical cross-correlations, as well. A physical interpretation of the latter effects is provided in terms of the differences in the spatial correlations of the ionic species within the interior of the pore. © 2012 American Chemical Society.